Dracula's children: Molecular evolution of vampire bat venom - Low, Dolyce H.W.; Sunagar, Kartik; Undheim, Eivind A.B.; Ali, Syed A.; Alagon, Alejandro C.; Ruder, Tim; Jackson, Timothy N.W.; Pineda Gonzalez, Sandy; King, Glenn F.; Jones, Alun; Antunes, Agostinho; Fry, Bryan G. (Journal of proteomics, 2013)
While vampire bat oral secretions have been the subject of intense research, efforts have concentrated only on two components: DSPA (Desmodus rotundus salivary plasminogen activator) and Draculin. The molecular evolutionary history of DSPA has been elucidated, while conversely draculin has long been known from only a very small fragment and thus even the basic protein class was not even established. Despite the fact that vampire bat venom has a multitude of effects unaccounted by the documented bioactivities of DSPA and draculin, efforts have not been made to establish what other bioactive proteins are secreted by their submaxillary gland. In addition, it has remained unclear whether the anatomically distinct anterior and posterior lobes of the submaxillary gland are evolving on separate gene expression trajectories or if they remain under the shared genetic control. Using a combined proteomic and transcriptomic approach, we show that identical proteins are simultaneously expressed in both lobes. In addition to recovering the known structural classes of DSPA, we recovered a novel DSPA isoform as well as obtained a very large sequence stretch of draculin and thus established that it is a mutated version of the lactotransferrin scaffold. This study reveals a much more complex secretion profile than previously recognised. In addition to obtaining novel versions of scaffolds convergently recruited into other venoms (allergen-like, CRiSP, kallikrein, Kunitz, lysozyme), we also documented novel expression of small peptides related to calcitonin, PACAP, and statherin. Other overexpressed protein types included BPI-fold, lacritin, and secretoglobin. Further, we investigate the molecular evolution of various vampire bat venom-components and highlight the dominant role of positive selection in the evolution of these proteins. Conspicuously many of the proteins identified in the proteome were found to be homologous to proteins with known activities affecting vasodilation and platelet aggregation. We show that vampire bat venom proteins possibly evade host immune response by the mutation of the surface chemistry through focal mutagenesis under the guidance of positive Darwinian selection. These results not only contribute to the body of knowledge regarding haematophagous venoms but also provide a rich resource for novel lead compounds for use in drug design and development. These results have direct implications in understanding the molecular evolutionary history of vampire bat venom. The unusual peptides discovered reinforce the value of studying such neglected taxon for biodiscovery. [Display omitted] •Principal and accessory glands remain under shared gene-expression control.•Majority of toxin types evolve under the influence of positive Darwinian selection.•Venom contains a wider suite of peptides and proteins than previously recognised.•Toxin types undergo mutation of surface chemistry through site-directed mutagenesis.•Venom is a rich source of novel molecules with significant potential for drug design.